The Emerging Role of Chronic Low-Grade Inflammation in the Pathophysiology of Polycystic Ovary Syndrome - Shorakae, Soulmaz; Teede, Helena; de Courten, Barbora; Lambert, Gavin; Boyle, Jacqueline; Moran, Lisa J. (Seminars in Reproductive Medicine, 2015)
Polycystic ovary syndrome (PCOS) has become increasingly common over recent years and is associated with reproductive features as well as cardiometabolic risk factors, including visceral obesity, dyslipidemia and impaired glucose homeostasis, and potentially cardiovascular disease. Emerging evidence suggests that these long-term metabolic effects are linked to a low-grade chronic inflammatory state with the triad of hyperinsulinemia, hyperandrogenism, and low-grade inflammation acting together in a vicious cycle in the pathophysiology of PCOS. Dysregulation of the sympathetic nervous system may also act as an important component, potentially creating a tetrad in the pathophysiology of PCOS. The aim of this review is to examine the role of chronic inflammation and the sympathetic nervous system in the development of obesity and PCOS and review potential therapeutic options to alleviate low-grade inflammation in this setting.
Keywords: polycystic ovary syndrome; obesity; chronic low-grade inflammation; sympathetic nervous system